2018
DOI: 10.17219/acem/69450
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the integrated antioxidant system of the body and the phenomenon of spa reaction in the course of radon therapy: A pilot study

Abstract: A beneficial effect of radon treatments on the growth of TAS in the body of the patients treated in the spa was demonstrated. The increase in the TAS concentration on the 5th day of treatment may indicate the relationship between these changes and the phenomenon of spa response. The changes are a result of low doses of ionizing radiation originating from radon dissolved in medicinal water, used in the course of the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…After 1 year, the symptoms of the patients greatly improved. Kuciel-Lewandowska et al 29 found that the conditions of patients with degenerative joints and disc disease who underwent treatment with radon water improved after 5 days. Moreover, the total antioxidant levels of patients also increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 year, the symptoms of the patients greatly improved. Kuciel-Lewandowska et al 29 found that the conditions of patients with degenerative joints and disc disease who underwent treatment with radon water improved after 5 days. Moreover, the total antioxidant levels of patients also increased.…”
Section: Discussionmentioning
confidence: 99%
“…These results coincided with the findings of several studies. 26-29 Yamaoka et al 30 reported that after 10 days, young men who bathed once a day for 40 minutes and inhaled 2080 Bq/m 3 of radon showed enhanced antioxidation function in the body as evidenced by increased SOD and CAT activities and inhibition of lipid peroxidation and total cholesterol production. The study participants’ exposure patterns of radon and results in Yamaoka’s study were very similar to our study.…”
Section: Discussionmentioning
confidence: 99%